Putative pyrophosphate phosphofructose 1-kinase genes identified in sugarcane may be getting energy from pyrophosphate - Suzuki, J. [UNESP]; Mutton, M. A. [UNESP]; Ferro, M. I T [UNESP]; Lemos, M. V F [UNESP]; Pizauro, J. M. [UNESP]; Mutton, M. J R [UNESP]; Di Mauro, S. M Z [UNESP] (My University, 2003)
Pyrophosphate-dependent phosphofructokinase (PPi-PFK) has been detected in several types of plant cells, but the gene has not been reported in sugar cane. Using Citrux paradixi PPi-PFK gene (AF095520 and AF095521) sequences to search the sugar cane EST database, we have identified both the α and β subunits of this enzyme. The deduced amino acid sequences showed 76 and 80% similarity with the corresponding α and β subunits of C. paradisi. A high degree of similarity was also observed among the PFK β subunits when the alignment of the sugar cane sequences was compared to those of Ricinus communis and Solanum tuberosum, it appears that α and β are two distinct subunits; they were found at different concentrations in several sugar cane tissues. It remains to be determined if the different gene expression levels have some physiological importance and how they affect sucrose synthesis, export, and storage in vacuoles. A comparison between the amino acid sequences of β PFKs from a variety of organisms allowed us to identify the two critical Asp residues typical of this enzyme's activity site and the other binding sites; these residues are tightly conserved in all members of this protein family. Apparently, there are catalytic residues on the β subunit of the pyrophosphate-dependent enzyme.
Keywords: ATP; PPi-PFK; Pyrophosphate phosphofructose 1-kinase; Sucrose; Sucrose synthase; Sugar cane; complementary DNA; inorganic pyrophosphatase; phosphotransferase; pyrophosphate fructose 6 phosphate 1 phosphotransferase; pyrophosphate-fructose 6-phosphate 1-phosphotransferase; pyrophosphate; pyrophosphate phosphofructose 1 kinase; sucrose; unclassified drug; amino acid sequence; enzymology; genetics; metabolism; molecular genetics; sugarcane; alpha chain; beta chain; carbohydrate synthesis; DNA library; energy metabolism; enzyme active site; enzyme binding; enzyme subunit; expressed sequence tag; gene expression; gene identification; grapefruit; nonhuman; plant genetics; plant tissue; potato; Ricinus communis; species comparison; tissue level; Amino Acid Sequence; DNA, Complementary; Molecular Sequence Data; Phosphotransferases; Pyrophosphatases; Saccharum; Arundinaria; Citrus x paradisi; Saccharum hybrid cultivar; Solanum; Solanum tuberosum